Theoretical and practical approaches to fiscal consolidation: The experience of Romania - Ionel Leonida (Financial Studies, 2018)
Fiscal consolidation is a traditional concern, we can say at the European institutional level, ratified and gradually taken over by the member countries, implemented through the Stability and Growth Pact, and enshrined in the Treaty of Maastricht, which is part of the permanent bailouts of national governments of the national and anchor budgeting of the European Union's fiscal policy. The importance of fiscal consolidation was strengthened with the manifestation of the effects of the financial and economic crisis started in 2008, through the strengthening and monitoring of fiscal discipline, being regulated by the European fiscal framework, to which Romania has also joined. The proposed approach on the issue of fiscal consolidation aims in the first part to present some theoretical and scientific fundamentals of this concept, and in the second part, the progress registered in Romania based on a set of specific indicators will be presented and evaluated. From a methodological point of view, the conceptual, logical, analytical and deductive approach will prevail. The results obtained can be a benchmark for assessing progress on fiscal consolidation and fiscal status at national level.
Keywords: E61; E62; H62; 330; fiscal consolidation; fiscal stance; fiscal framework; fiscal rules